KH. Abdul Kabier and His Contribution to the Development of Islamic Education Institutions in Banten (1942-1975) - Muhamad Nandang Sunandar; Nurlaillatul Barokah; Didin Saepudin; Ahmad Yury Alam Fathallah (Historia Madania: Jurnal Ilmu Sejarah, 2026)
KH Abdul Kabier is a visionary scholar in the world of Islamic education in Banten, by pioneering a boarding school currently known as Pondok Pesantren Nur El Falah which began as a Ta'lim Assembly and Diniyah Madrasah which he founded in 1943. KH Abdul Kabier, an alumnus of Tebu Ireng boarding school in Jombang, East Java, is a cleric who is active in developing Islamic educational institutions, especially Islamic boarding schools, where the boarding school he attended became one of the centers of Islamic learning that gave birth to many Muslim scholars and scholars in Indonesia, especially in Banten. One of his students is KH Ma'ruf Amien, the former vice president of Indonesia for the 2019- 2024 period. This research uses historical research methods, which consist of data collection (heuristics), source criticism (verification), analysis (interpretation) and historical writing (historiography). KH. Abdul Kabier contributed to developing Islamic educational institutions by establishing several levels of Islamic education ranging from MI, MD, MTS, SMP, MA, SMA, SMK to the KH. Abdul Kabier Islamic College (STAIKHA) which until now still exists and contributes to the world of Islamic education Keywords: KH. Abdul Kabier, Islamic Education Institution, Islamic Boarding School, Nur El Falah.